Language Curriculum and Material Development: A Book Review - Andi, Adisaturrahimi (CV Insan Kreasi Media, 2023)
A book review is a type of literary criticism in which the merit, style, and content of a book are evaluated. Language curriculum design is becoming increasingly important these days. This is supported by a number of authors who have written books on language curriculum design, one of which is